Pengaruh Pemberian Posisi Duduk 3 Menit Setelah Induksi Spinal Anestesi Terhadap Pencegahan Hipotensi Pada Pasien Sectio Caesarea Di RSUD Tgk. Abdullah Syafi’i Beureuneun Kabupaten Pidie Provinsi Aceh - Fadlillah, Fadlillah; Handayani, Rahmaya Nova; Aprilyani, Ita (Universitas Harapan Bangsa Purwokerto, 2023)
Hypotension is one of the side effects of spinal anesthesia. Giving a sitting position for three minutes after spinal injection is one of the actions taken to reduce the incidence of hypotension. The aim of this study was to determine the effect of giving a sitting position 3 minutes after induction of spinal anesthesia on the prevention of hypotension in sectio caesarea patients at Tgk. Abdullah Syafi'i Beureuneun, Pidie District, Aceh Province. This research method is a Quasi Experiment with a Posttest-Only Control Design approach. The number of samples in this study were 80 sectio caesarea patients who were divided into 2 groups, namely 40 experimental groups and 40 control groups. The instrument used in this study was an observation sheet on the incidence of hypotension in patients with sectio caesarea. Data analysis was performed univariately and bivariately using the Mann-Whitney test. The results showed that the characteristics of respondents based on age found the majority aged 20-35 years as many as 74 respondents (92.5%), based on the number of children or parity the majority were multipara (2-5) as many as 66 respondents (82.5%) and based on the education of the majority SMA as many as 59 respondents (73.3%). There is an effect of sitting position 3 minutes after induction of spinal anesthesia on the prevention of hypotension in sectio caesarea patients with a p-value of 0.000 (P<0.05). This study concluded that there was an effect of sitting position 3 minutes after induction of spinal anesthesia on the prevention of hypotension in sectio caesarea patients at Tgk. Abdullah Syafi'i Beureuneun, Pidie District, Aceh Province.